Exploring the Use of Meditation as a Valuable Tool to Counteract Sedentariness - Bigliassi, Marcelo; Bertuzzi, Romulo (Frontiers in Psychology, 2020)
Some forms of meditation have been recently proposed as effective tools to facilitate the handling of undesired thoughts and reappraisal of negative emotions that commonly arise during exercise-related situations. The effects of meditation-based interventions on psychological responses could also be used as a means by which to increase exercise adherence and counteract the detrimental consequences of sedentariness. In the present article, we briefly describe the effects of meditation on physical activity and related factors. We also propose a theoretical model as a means by which to further understanding of the effects of meditation on psychological, psychophysical, and psychophysiological responses during exercise. The results of very recent studies in the realms of cognitive and affective psychology are promising. The putative psychological mechanisms underlying the effects of meditation on exercise appear to be associated with the interpretation of interoceptive and exteroceptive sensory signals. This is primarily due to the fact that meditation influences the cerebral processing of physical sensations, emotions, and thoughts. In such instances, the bodily and perceptual responses that are commonly reported during exercise might be assuaged during the practice of meditation. It also appears that conscious presence and self-compassion function as an emotional backdrop against which more complex behaviours can be forged. In such instances, re-engagement to physical activity programmes can be more effectively achieved through the implementation of holistic methods to treat the body and mind. The comments provided in the present paper might have very important implications for exercise adherence and the treatment of hypokinetic diseases.